Comparison of dental anesthetic efficacy between the periodontal intraligamentary anesthesia and other infiltration anesthesia: a systematic review and meta-analysis - Jialei Pan; Yan Wang; Yuran Qian; Jing Zou; Qiong Zhang (PeerJ, 2023)
Background Uncertainty exists regarding the pain scores and the success rate of intraligamentary anesthesia compared to other infiltration anesthesia. Based on the conditions of clinical anesthesia techniques, we conducted a systematic review and meta-analysis to compare the efficacy of intraligamentary anesthesia with other infiltration anesthesia. Methods The search was carried out in PubMed Central, Cochrane Central Register of Controlled Trials, MEDLINE (via OVID), Embase (via OVID), and Scopus from the inception to March 26, 2023. Results Seven eligible randomized controlled trials were included in the meta-analysis. The results indicated no significant difference in the success rate (RR = 0.96; 95% CI [0.81–1.14]; p = 0.65; I2= 73%) and visual analog scale (VAS) during dental procedures (MD = 3.81; 95% CI [−0.54–8.16]; p = 0.09; I2= 97%) between intraligamentary anesthesia and other infiltration anesthesia. However, intraligamentary anesthesia exhibited a higher VAS score during injection than other infiltration anesthesia (MD = 8.83; 95% CI [4.86–12.79]; p < 0.0001; I2= 90%). A subgroup analysis according to infiltration techniques showed that supraperiosteal anesthesia had a lower VAS score during dental procedures than intraligamentary anesthesia. Conclusions Intraligamentary anesthesia and other infiltration anesthesias have the same success rate and pain during dental procedures. However, the pain during injection of intraligamentary anesthesia is heavier than that of other infiltration anesthesia.